KORELASI INDEKS MASSA TUBUH DENGAN KEKUATAN GENGGAMAN TANGAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH - Suharni, Suharni; Daffa Putra Dianto; Alief Dhuha (Nusantara Hasana Journal, 2025)
Body Mass Index (BMI) is a primary anthropometric parameter used to quantify an individual's nutritional status by assessing body mass relative to height. Handgrip strength has been identified as a significant indicator that reflects overall physical fitness and is associated with various health outcomes. This study aims to examine the relationship between BMI and handgrip strength among medical students of the Faculty of Medicine, Baiturrahmah University, class of 2024. This study employed an analytical observational design with a cross-sectional approach. Samples were selected using a systematic random sampling technique. A total of 46 participants were included in the study. Handgrip strength was measured using a Camry EH101. Data analysis was conducted using SPSS version 27.0, and Spearman’s correlation test was utilized to assess the relationship between BMI and handgrip strength. The result of the study conclude that The majority of participants were female, totaling 38 individuals (82.6%). The most common age among participants was 19 years, with 27 individuals (58.7%). The mean BMI for male participants was 25.71 kg/m², while for female participants it was 22.13 kg/m². The overall mean BMI for all participants was 22.76 kg/m². The average handgrip strength among male participants was 40.82 kg, compared to 27.90 kg for female participants, with an overall mean handgrip strength of 30.14 kg. The predominant BMI classification for both male and female participants was within the normal range. Regarding handgrip strength classification, the majority of male participants (62.5%) fell within the 40–49.9 kg category, while most female participants (60.5%) were classified within the 20–29.9 kg range. A significant positive correlation was found between BMI and handgrip strength in female participants (r = 0.728, p = 0.001) and in the overall participant group (r = 0.714, p = 0.001), whereas no significant correlation was observed among male participants (r = 0.359, p = 0.389). Therefore, it can be concluded that There is a strong and significant positive correlation between BMI and handgrip strength among the medical students of the Faculty of Medicine, Baiturrahmah University, class of 2024.